Stable layered Ni-rich LiNi0.9Co0.07Al0.03O2 microspheres assembled with nanoparticles as high-performance cathode materials for lithium-ion batteries. Issue 6 (18th January 2017) - Zhou, Pengfei; Meng, Huanju; Zhang, Zhen; Chen, Chengcheng; Lu, Yanying; Cao, Jun; Cheng, Fangyi; Chen, Jun
Abstract : Stable layered LiNi0.9 Co0.07 Al0.03 O2 microspheres show large discharge capacity and good cycling performance as cathode for lithium ion batteries. Abstract : The layered LiNi1− x − y Co x Al y O2 family with advantages of high capacity and low cost is considered as a promising cathode material for lithium-ion batteries (LIBs) for powering electric vehicles. However, such layered oxides still suffer from poor cycle stability and thermal instability during cycling. Herein, we report an easy coprecipitation synthesis of an Ni-rich microspherical Ni0.9 Co0.07 Al0.03 (OH)2 precursor with uniform particle size and large BET specific surface area via employing AlO2 − as the Al source. The uniform and dense LiNi0.9 Co0.07 Al0.03 O2 microspheres with well-assembled nanoparticles and low degree of Ni 2+ /Li + mixing are synthesized by optimizing the calcination conditions. As a cathode material for LIBs, LiNi0.9 Co0.07 Al0.03 O2 delivers an appealing initial reversible capacity (236 mA h g −1 at 0.1C), good cyclic stability at various temperatures ( e.g. capacity retention of 93.2% at 25 °C and 83.8% at 55 °C after 100 cycles at 1C), high rate capability (140 mA h g −1 at 10C), and excellent thermal stability (heat generation of 517.5 J g −1 at 4.3 V). Such superior electrochemical performance is mainly attributed to the combination of the high Ni component, layered structure with low degree of Ni 2+ /Li + mixing, and uniform microspheres with homogeneous distribution of Ni, Co, and Al. Moreover, the full cell of LiNi0.9 Co0.07 Al0.03 O2 /KS6 has been assembled, delivering a high capacity of 210 mA h g −1 at 0.1C and excellent cycle stability.